Presence of Porphyromonas and Prevotella species in the oral microflora of cattle with periodontitis - Borsanelli, Ana Carolina [UNESP]; Júnior, Elerson Gaetti-Jardim [UNESP]; Schweitzer, Christiane Marie [UNESP]; Döbereiner, Jürgen; Dutra, Iveraldo S. [UNESP] (FapUNIFESP (SciELO), 2015)
Bovine periodontitis is a progressive purulent infectious process associated with the presence of strictly and facultative anaerobic subgingival biofilm and epidemiologically related to soil management in large geographic areas of Brazil. This study aimed to detect species of the genera Porphyromonas and Prevotella, which occurr in periodontal pockets of cattle with lesions deeper than 5mm (n=26) and in gingival sulcus of animals considered periodontally healthy (n=25). Presence of the microorganisms was evaluated by independent- culture medium diagnostic method, using polymerase chain reaction (PCR) with specific primers of Porphyromonas asaccharolytica, P. endodontalis, P. gingivalis, P. gulae, Prevotella buccae, P. intermedia, P. loescheii, P. melaninogenica, P. nigrescens, P. oralis and P. tannerae. The species P. endodontalis (80.7%), P. melaninogenica (73.1%) and P. intermedia (61.5%) were the most predominant in samples of cattle with periodontitis. Regarding non -injured gingival sulcus of cattle, P. endodontalis (40%) and P. loeschei (40%) prevailed. Porphyromonas gingivalis, P. gulae and Prevotella tannerae were not detected in the 51 samples studied. Data evaluation by T test, enabled to verify that ocorrence of Porphyromonas asaccharolytica (p=0.000003), P. endodontalis (p=0.0023), Prevotella buccae (p=0.0017), P. intermedia (p=0.0020), P. melaninogenica (p=0.00006) and P. oralis (p=0.0028) is correlated with bovine periodontitis.
Keywords: Cattle; Periodontitis; Porphyromonas spp.; Prevotella spp.